Disclosure of banking risks in accordance with the requirements of the seventh international financial reporting standard (IRFS7) - Ali Mahmood Hasen; Mohamed Elnair Mohamed Elnour (Journal of Madenat Alelem University College, 2022)
The research sought to discover the extent to which Iraqi private commercial banks apply quantitative and qualitative disclosures about risks in accordance with the seventh international standard. It proceeded from the problem that there are differences in the commitment of the Iraqi banking sector to abide by the disclosures for each type of banking risk (market risk, credit risk and liquidity risk). And in order to prove the hypothesis of the research, which stipulates that "banks are committed to the requirements of the seventh International Financial Reporting Standard (IFRS7), the requirements related to disclosures about banking risks." The descriptive approach was adopted by examining the bank reports of the research sample, which was selected by the cluster sampling method, and it was 6 Iraqi commercial banks. The research found that the Commercial Bank of Iraq and the Gulf Bank were the only ones who disclosed quantitative and qualitative disclosures about banking risks, and their disclosure began since 2016. The research recommended the need to work on applying disclosure according to the seventh international financial reporting standard accurately, as the standard is between quantitative and qualitative disclosure and the requirements for their disclosure, and that the lack of commitment of banks to this type of disclosure wastes the role of management and weakens its ability to deal with different types of banking risks.